Analisis Keterkaitan Profil Dan Kinerja Peritel Di Pasar Tradisional - Adi Zakaria Afiff; Rizal Edy Halim (Universitas Airlangga, 2010)
The growing retail industry in Indonesia has two consequences; increase regional income which debatable issue, on the other side potentially decrease the performance of retailers (read: pedagang) in traditional wet market. This study not to conclude why the previous condition emerge, but explore why the performance of retailers in traditional wet market decreased. Using 315 respondents and intercept technique, the study found that there are two problems faced by retailers in traditional wet market today. The first one is their entrepreneurial orientation seems too low, the secondly their market orientation also couldn’t boosting their performance. The findings also shown retailers with higher entrepreneurial orientation and market orientation had a higher performance.